VISUAL EXPERIENTIAL IN DIGITAL DOCUMENTATION FOR RURAL TOURISM PROMOTION OF BA’KELALAN, SARAWAK - Doris, Maying; Yakup, Mohd Rafee; Mohd Affendi, Azizan; Awangko Hamdan, Awang Arshad; Mohamad Zamhari, Abol Hassan (UNIMAS Publisher, 2021)
This paper aims to share some research information based on the visual experiences during the field trip to Ba’Kelalan, Sarawak. Ba’Kelalan is a traditional village of the Lun Bawang community and is well-known as an eco-tourism area in Sarawak. All the experienceswere documented using the digital documentationtools and have been recorded with reference tothe formalistic artistic methods; in ensuring thevisual effects have the best quality and high artistic value. The results will be discussed based on theimplemented process and the impact of digital document preparation through experientiallearning theory. Next, this article will provide newideas and visual insights that can help data enhancement, especially in the promotion of the rural tourism